Feasibility of centre-based incident reporting in primary healthcare: the SPIEGEL study. Issue 2 (5th January 2011) - Zwart, Dorien L M; Steerneman, Anke H M; van Rensen, Elizabeth L J; Kalkman, Cor J; Verheij, Theo J M
Abstract : Objective: To evaluate the feasibility of a locally implemented incident-reporting procedure (IRP) in primary healthcare centres after 1 year. Setting and participants: Five primary healthcare centres caring for more than 43 000 patients in The Netherlands. GPs, medical nurses, physiotherapists, pharmacists, pharmacist assistants and trainees reported incidents (a total of 117 employees). Methods: An IRP was implemented in which participants were encouraged to report all incidents. In addition, dedicated 'reporting weeks' were introduced that emphasised reporting of minor incidents and near misses. In every centre, an IRP committee analysed the reported incidents in order to initiate improvements when necessary. Outcome measures: Frequency and nature of reported incidents, number of incidents analysed by the IRP committees and number of improvements implemented. In addition, the authors studied the actual implementation of the IRP and the acceptability as experienced by participants. Results: A total of 476 incidents were reported during a 9-month reporting period. Of all incidents, 62% were reported in a reporting week, and most were process-related. Possible harm for patients was none or small in 87% of the reported incidents. IRP committees analysed 84 incidents and found 230 root causes. All participating centres had initiated improvement projects as a result of reported incidents. Most interviewees considered the IRP feasible, but several practical, professional and personal barriers to implementation of the IRP were identified. Conclusion: The implementation of a centre-based IRP in primary care is feasible. Reporting weeks enhance the willingness to report.